Constitutional jurisprudence of the Federal Republic of Germany - Kommers, Donald P. (Duke University Press, 2012)
The third edition of this renowned English-language guide to German constitutional law has been fully updated and significantly expanded to incorporate previously omitted topics and recent decisions of the German Federal Constitutional Court.